Ethanol Extraction of Active Ingredients and Antioxidants from Germinated Sangyod Rice - Chairerk, Nirana; Pongyeela, Prukraya; Chungsiriporn, Juntima; Rakmak, Nirattisai (Applied Science and Engineering Progress, 2021)
Sangyod rice is a special red rice variety, originally planted in Pattalung province of Thailand. This type of rice is high in nutrients and antioxidants. This research aimed to produce a rice extract by solvent extraction of germinated Sangyod rice. For the extraction, ethanol at the concentrations 0, 50, or 95% (v/v) was used. Various extraction times and rice-to-solvent ratios, as well as solvent reuse and recovery were studied. The results show that the extract from germinated Sangyod rice has higher TPC, TFC, and GABA contents and higher antioxidant activity than not germinated or Riceberry rice. An 0.5 h extraction time with rice-tosolvent ratio 1:15 (g/mL) were optimal for extracting germinated Sangyod rice. The 50% ethanol solvent gave the highest TPC, TFC, GABA and DPPH antioxidant activities, at 1,627.00 ± 53.08 mg GAE/100 g rice, 559.50 ± 17.06 mg QE/100 g rice, 9.97 ± 0.17 mg GABA/100 g rice, and 0.16 ± 0.01 mg/mL, respectively. Regarding stability of the rice serum, temperature affected stability of the extracts. The results of this study can provide new opportunities to promote Sangyod rice to farmers and add value to rice products. The extract has potential as an active ingredient in cosmetics.